2019
DOI: 10.1162/jocn_a_01369
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and Ambiguous Threat Processing: Functionally Dissociable Roles of the Amygdala and Bed Nucleus of the Stria Terminalis

Abstract: Highly influential models have proposed that responses to different types of threat are mediated by partially segregated neural systems, with the amygdala underlying phasic responses to explicit threat (fear) and the bed nucleus of the stria terminalis (BNST) mediating sustained responses to ambiguous threat (anxiety). However, newer models have suggested similar recruitment of both regions across a wide spectrum of threat. Therefore, to empirically test these models and further elucidate the activation profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…This suggests a unique role for BNST-projecting neurons of the IL [which 423 appear to be glutamatergic: (Crowley et al, 2016;Glangetas et al, 2017)] in processing excitatory 424 backwards CSs. There is growing evidence for a regulatory role for prefrontal connections to the 425 BNST in stress and anxiety-like behavior (Fox et al, 2010;Glangetas et al, 2017Glangetas et al, , 2013Johnson 426 et al, 2018;Kinnison et al, 2012;Motzkin et al, 2015;Naaz et al, 2019;Radley et al, 2009), the 427 present data adds to this work by suggesting that the IL may be involved in generating freezing 428 and/or stress responding to the backward CS. This would stand in contrast to considerable data 429 indicating that the IL is involved in the inhibition of freezing behavior after extinction, for example 430 (Milad and Quirk, 2002;Quirk and Mueller, 2008).…”
Section: Backward Css Selectively Increase Fos Expression In Mpfc Affmentioning
confidence: 57%
See 1 more Smart Citation
“…This suggests a unique role for BNST-projecting neurons of the IL [which 423 appear to be glutamatergic: (Crowley et al, 2016;Glangetas et al, 2017)] in processing excitatory 424 backwards CSs. There is growing evidence for a regulatory role for prefrontal connections to the 425 BNST in stress and anxiety-like behavior (Fox et al, 2010;Glangetas et al, 2017Glangetas et al, , 2013Johnson 426 et al, 2018;Kinnison et al, 2012;Motzkin et al, 2015;Naaz et al, 2019;Radley et al, 2009), the 427 present data adds to this work by suggesting that the IL may be involved in generating freezing 428 and/or stress responding to the backward CS. This would stand in contrast to considerable data 429 indicating that the IL is involved in the inhibition of freezing behavior after extinction, for example 430 (Milad and Quirk, 2002;Quirk and Mueller, 2008).…”
Section: Backward Css Selectively Increase Fos Expression In Mpfc Affmentioning
confidence: 57%
“…This contrasts with prior work suggesting that the BNST 367 only mediates freezing behavior to long-duration cues or contexts (Hammack et al, 2015;Waddell 368 et al, 2006). However, recent data in other paradigms suggest a role for the BNST in the processing 369 of responses to relatively brief threat stimuli (Brinkmann et al, 2018;Choi et al, 2014;Haufler et 370 al., 2013;Kinnison et al, 2012;Kiyokawa et al, 2015;Klumpers et al, 2017;Luyck et al, 2018bLuyck et al, , 371 2018aNaaz et al, 2019). Together, these data suggest that stimulus duration is not necessarily a 372 determinant of BNST involvement.…”
Section: Backward Css Selectively Increase Fos Expression In Mpfc Affmentioning
confidence: 87%
“…Evidence suggests that these two regions have distinct roles in threat perception, specifically phasic versus sustained response(Alvarez, Chen, Bodurka, Kaplan, & Grillon, 2011;Herrmann et al, 2016;Naaz, Knight, & Depue, 2019). In sum, we provide evidence that the extended amygdala circuitry facilitates speed of response in threatening situations and, for the first time, highlight a key role for the stria terminalis in the efficient recognition of emotion under threat.…”
mentioning
confidence: 52%
“…The extended amygdala network includes the amygdala and the BNST. Evidence suggests that these two regions have distinct roles in threat perception, specifically phasic versus sustained response (Alvarez, Chen, Bodurka, Kaplan, & Grillon, 2011;Herrmann et al, 2016;Naaz, Knight, & Depue, 2019). The most recent paper by Naaz et al (2019) found that the amygdala is involved in phasic responses to explicit (cued) threat and the BNST involved in sustained responses to ambiguous threat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation